The effect of autism on language delay with children in Dohuk Governorate Center (Raparin Journal of Humanities (RJH), 2024)
Autism is considered a new disorder that affects some children and greatly affects their mental development and language delay. Neglecting autism treatment may lead to serious complications, including madness. This research focuses on the effect of autism on linguistic delay among children at the Dohuk Governorate Autism Center. The research relied on the descriptive approach using a questionnaire that was distributed to special education and autism teachers in the Dohuk Governorate Education Directorate, and the data was analyzed statistically to understand the relationship between autism and language delay. The aim of the research is to know the ways of developing autism and its effect on language delay with children in the Dohuk Governorate Center, and to educate their families about the dangers of autism and ways to prevent it to protect their children from negative effects on their language and health. The results showed that language impairment is one of the main symptoms of autism, with 67% of specialist teachers answering this question “yes”. This research consists of two chapters, in addition to the introduction and conclusion. The first chapter includes the theoretical aspect and deals with autism and language delay, while the second chapter includes the analytical aspect and deals with statistical analysis and the presentation and discussion of the results.